Storage and query over encrypted sensitive association rules in database. (23rd August 2019) - Bansal, Meenakshi; Grover, Dinesh; Sharma, Dhiraj
In this modern era of increasing need of data sharing along with data security, processing over encrypted data is highly desirable. Data encryption is the most common technique used for maintaining the data privacy. However, when processing is required to be done on this encrypted data it becomes a critical task. In most of the existing theories data need to be decrypted before it is being processed. Decryption before processing leads to serious threat to data. To avoid this, a new mechanism has been proposed and implemented which provides strong data protection. This mechanism helps to query over encrypted data without decrypting it. Experimental results show that the new technique outperforms the existing one in terms of query performance, computation time and storage memory.